‘CUIUS REGIO EIUS RELIGIO?’ - ZJAZD HISTORYKÓW PAŃSTWA I PRAWA, LUBLIN 22-24 WRZEŚNIA 2006 ROKU - Elżbieta Loska (Zeszyty Prawnicze)
‘CUIUS REGIO EIUS RELIGIO?’ - ZJAZD HISTORYKÓW PAŃSTWA I PRAWA, LUBLIN 22-24 WRZEŚNIA 2006 ROKU